Manageral Intelligence and Work Communiation Related to Foresight the Future of Employees - Promsit, Surapit (Journal of Humanities and Social Sciences Thonburi University, 2022)
The research objectives were to compare the level of employee’s foresight by demographic variables and to predict the employee’s foresight by using managerial intelligence and work communication in a group setting. The sample group comprised of 421 employees of government, private sector and state enterprise and was divided by stratified random sampling from the selected types of employment and gender. The statistical summary used to prove the hypotheses was the measurement of mean comparison, significantly different levels, analysis of variance (One-way ANOVA), correlation coefficient, and multiple regression analysis. The result showed that (1) employee with spouses had the ability to foresight the future higher than a single employee at a significant level of .05. (2) Employee with experience of more than 10 years had the foresight higher than the employee with experience of 10 years or under, at the significance level of .05. (3) Baby Boomer employees had the ability to foresight the future higher than the employee in generation Y and generation Z at the significance level of .01 and 0.05 and (4) Work moral, emotional quotient, adaptability, team collaboration and work communication can predict the employee foresight at 44.7 percentage.